Mobile Phones and Economic Development: Evidence From the Fishing Industry in India - Reuben Abraham (Information Technologies and International Development Volume 4, Number 1, Fall 2007, 5-17, 2007)
There is considerable speculation about the correlation between investments in telecommunications and economic development. Yet, there has been very little research on whether there is a connection between information and communication technologies (ICTs) and economic growth, and if indeed a connection can be established, how it works. Vast populations in developing countries live in rural areas and are subject to the vagaries of their highly inefcient markets. Mobile phones, by virtue of their role as carriers and conduits of information, ought to lessen the information asymmetries in markets, thereby making rural and undeveloped markets more efcient. This article tests this assumption using a case-study from India, where the shing community in the southwestern state of Kerala has adopted mobile phones in large numbers. Using mobile phones at sea, shermen are able to respond quickly to market demand and prevent unnecessary wastage of catch-sh being a highly perishable commodity-a common occurrence before the adoption of phones. At the marketing end, mobile phones help coordinate supply and demand, and merchants and transporters are able to take advantage of the free ow of price information by catering to demand in undersupplied markets. There is also far less wastage of time and resources in all segments of the shing community. Fishermen spend less time idling on shore and at sea, whereas owners and agents go to the landing centers only when they receive information (via mobile phones) that their boats are about to dock. We nd that with the widespread use of mobile phones, markets become more efcient as risk and uncertainty are reduced. There is greater market integration; there are gains in productivity and in the Marshallian surplus (sum of consumer and producer surplus); and price dispersion and price uctuations are reduced. The potential efciencies are, however, subject to easy access to capital, especially at the production end of the supply chain, without which the market remains less efcient than it could be. Finally, the quality of life of the shermen improves as they feel less isolated and less at risk in emergencies